Electrical properties of polyethylene and polypropylene blend nanocomposites with fillers for high voltage insulation - Hizamul-din, Hanis Hamizah (2020)
This study investigated the electrical properties of polypropylene and low density polyethylene (PP/LDPE) nanocomposite filled with zirconium dioxide and silicon dioxide and compare the test results of these two fillers. All samples are tested in four different test to get the optimum results. The first test is conducted using Differential Scanning Calorimetry (DSC) to examine their melting point and degree of crystallinity. Next, Scanning Electron Microscopy (SEM) is utilizes to observe and compare their structure analysis. After that, direct current breakdown test is carried out and the results are analysed through Weibull analysis. Lastly, permittivity test is conducted using Gamry Instrument. According to results obtained, polymer nanocomposites with fillers shows significant improvement on their performance compared to the one without fillers. Besides that, zirconium dioxide shows better results than silicon dioxide throughout the tests.